Smaller rostral cingulate volume and psychosocial correlates in veterans at risk for suicide. (February 2023) - Goldstein, Kim E.; Feinberg, Abigail; Vaccaro, Daniel H.; Ahmed, Tasnova; Chu, King-Wai; Goodman, Marianne; Govindarajulu, Usha; Challman, Katelyn N.; Haghighi, Fatemeh; Yehuda, Rachel; Szeszko, Philip R.; Osterberg, Terra; et al.
Highlights: Depressed Veterans with suicide attempt history exhibit smaller rostral anterior cingulate. Less left rostral anterior cingulate cortex gray matter volume predicts suicide attempt history. Lower levels of grit in depressed US Veterans predicts to suicide attempt history. Abstract: Suicide research/clinical work remain in dire need of effective tools that can better predict suicidal behavior. A growing body of literature has started to focus on the role that neuroimaging may play in helping explain the path towards suicide. Specifically, structural alterations of rostral anterior cingulate cortex (rost-ACC) may represent a biological marker and/or indicator of suicide risk in Major Depressive Disorder (MDD). Furthermore, the construct of "grit, " defined as perseverance for goal-attainment and shown to be associated with suicidality, is modulated by rost-ACC. The aim was to examine relationships among rost-ACC gray matter volume, grit, and suicidality in U.S. Military Veterans. Participants were age-and-sex-matched Veterans with MDD: with suicide attempt (MDD+SA: n  = 23) and without (MDD-SA: n  = 37). Groups did not differ in depression symptomatology. Participants underwent diagnostic interview, clinical symptom assessment, and 3T-MRI-scan. A Group (SA-vs.-No-SA) x Cingulate-region (rostral-caudal-posterior) x Hemisphere (left-right) mixed-model-multivariate-ANOVA was conducted. Left-rost-ACC was significantly smaller in MDD+SA, Group x Cingulate-region x Hemisphere-interaction. Lower grit and less left-rost-ACC gray matter each predicted suicide attempt history, but grit level was a more robust predictor of SA. Both structural alterations of rost-ACC and grit level represent potentially valuable tools for suicide risk assessment.